Triple-attention interaction network for breast tumor classification based on multi-modality images. (July 2023) - Yang, Xiao; Xi, Xiaoming; Wang, Kesong; Sun, Liangyun; Meng, Lingzhao; Nie, Xiushan; Qiao, Lishan; Yin, Yilong
Highlights: A novel triple-attention interaction network is proposed for breast tumor classification with ADC and DWI images. A novel triple inter-modality interaction mechanism is proposed to leverage correlation, complementary, and discriminative information. An intra-modality interaction mechanism is introduced to improve the discriminative ability of single-modality features. Graphical abstract: Abstract: Breast cancer can be diagnosed using medical imaging. Classification performance of medical imaging can be improved by multi-modality image fusion. However, existing fusion algorithm fail to consider the importance of modality interactions and cannot fully utilize multi-modality information. Attention mechanisms can effectively explore and combine multi-modality information. Thus, we propose a novel triple-attention interaction network for breast tumor classification based on diffusion-weighted imaging (DWI) and apparent dispersion coefficient (ADC) images. A triple inter-modality interaction mechanism is proposed to fully fuse the multi-modality information. Three modal interactions were performed through the developed inter-modality relation module, channel interaction module, and multi-level attention fusion module to explore the correlation, complementary, and discriminative information, respectively. Additionally, we introduce a novel dual parallel-attention module for the incorporation of spatial and channel attention to improve the discriminative ability of single-modality features. Using these mechanisms, the proposed algorithm can mine and explore useful multi-modality information fully, to improve classification performance. Experimental results demonstrate that our algorithm outperforms other multi-modality fusion algorithm, and extensive ablation studies were conducted to verify the advantages of our algorithm. The area under the receiver operating characteristic curve, accuracy, specificity, and sensitivity were 90.5%, 89.0%, 85.6%, and 92.4%, respectively.